MODEL PENGEMBANGAN MODAL SOSIAL MELALUI PERAN DAN PARTISIPASI POT (PAGUYUPAN ORANG TUA) UNTUK MENINGKATKAN KUALITAS PENDIDIKAN: (Studi di SDI Ma’arif Plosokerep Kota Blitar Sekolah Berstandar Internasional ) - Novi Catur Muspita (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2019)
This research background is the phenomenon of the role and participation of guardians of students in the field of education is very important and strategic. The success of the work performance of the Education Management is inseparable from the professional ability of the individuals involved in the activity. The objectives of this study are: (1) To determine the design of the social capital development model through the role and participation of POT (Parents' Association) as to Improve the Quality of Education (Study in SDI Ma’arif Plosokerep Kota Blitar), (2) To find out constraints in developing social capital through the role and participation of POT (Parents' Association) to improve quality of Education (Study at Study in SDI Ma’arif Plosokerep Kota Blitar) . The results of this study that in designing Social Capital Development Models through Role and POT Participation ( Parents Association) to Improve Education Quality in SDI Ma'arif Plosokerep Kota Blitar consists of several elements of social capital in strengthening education, among others: (1) participation in a network, (2) reciprocity, (3) trust, ( 4) social norms, (5) Proactive action, the constraints in implementing the Design of the Social Capital Development Model Through the Role and Participation of POT to Improve the Quality of Education in SDI Ma'arif Plosokerep Kota Blitar are: (1) Lack of understanding of the guardian of the importance of POT (2) Parent has an impact on / quantity of active student guardians (3) Insensity of POT meeting which is POT period meeting / meeting, (4) Not all teachers and Wali kelas comprehensively understand POT, (5) No schema and SOP for POT formation, work system and mechanism